RESPONSIVENESS AND PROFESSIONALISM INFLUENCE PATIENT SATISFACTION AT KLINIK PRATAMA BANDUNG - Moch Ikhsan Juliansyah; Zulmansyah; Muhardi (UPT Publikasi Ilmiah UNISBA, 2026)
Service quality is a critical determinant of patient satisfaction, particularly in primary healthcare. This study examines the effects of four service quality dimensions (tangible, responsiveness, assurance, and professionalism) on patient satisfaction at Klinik Pratama Sehat Margasari in Bandung. A quantitative design was employed with purposive sampling of 92 patients who completed a structured questionnaire. Data were analyzed using descriptive statistics and multiple linear regression to estimate the unique and joint effects of each dimension. Descriptively, tangible, assurance, and professionalism were rated very good, while responsiveness was rated good. Regression results indicate that responsiveness and professionalism significantly increase patient satisfaction, whereas tangible and assurance are not statistically significant. Jointly, the four dimensions have a significant overall effect. These findings suggest that non-physical factors are more decisive for patient satisfaction than physical facilities alone. The study highlights managerial implications for primary healthcare: prioritize service behaviors and professional conduct to raise patient satisfaction in resource-constrained settings.